S14* Cumulative Genetic Risk of Asthma Severity in Children and Young People. (12th November 2015) - Collis, VL; Cunningham, JO; Dumble, S; Tavendale, R; Vijverberg, SJH; Maitland-van der Zee, AH; Smith, HE; Turner, SW; Palmer, CNA; Mukhopadhyay, S
Abstract : Introduction and objectives: Single nucleotide polymorphisms (SNPs) in Chitinase 3-like-1 ( CHI3L1), Matrix Metalloproteinase 9 (MMP9) and Matrix Metalloproteinase 12 ( MMP12) act on the biological process of airway remodelling that is linked to asthma exacerbations. The cumulative presence of these SNPs could help identify patients at increased risk of asthma exacerbations. The aim of this study is to assess whether these genetic variants increase the risk of asthma exacerbations in children and young adults and exert a cumulative effect on this risk. Methods: Gene-environmental interactions were investigated in three observational asthma cohorts (BREATHE, PAGES, PACMAN), across three European countries (England, Scotland and the Netherlands), and a pooled dataset including, in total 2, 701 patients with asthma, aged between 3 and 22 years (recruited between 2003 and 2011). Participants were genotyped for four biologically related SNPs in three genes ( CHI3L1, MMP9 and MMP12 ). Results: In single SNP analysis all four investigated SNPs were associated with markers of asthma severity. In the BREATHE study the four investigated SNPs showed a cumulative association with exacerbations involving the use of a course of oral steroids, asthma-related absence from school/college/work, overall asthma exacerbations (OR for overall exacerbations with four risk variants compared to zero risk variants = 3.14, p < 0.001) and asthma treatment step (p value for trend = 0.036). Furthermore, a combined meta-regression analysis of the four investigated SNPs in the pooled dataset (n = 2701) replicated this cumulative association with exacerbations requiring hospital admission (OR per genotypic step 1.18; p = 0.046) and exacerbations requiring oral steroids (OR per genotypic step 1.19; p = 0.008). Conclusions: Analysis of these four SNPs could enable clinicians to identify patients at higher risk of a severe asthma phenotype, potentially helping tailor strategies for improved asthma control. *S14- BTS Medical Student Award Winner